Impact of California Statute on Naloxone Availability and Opioid Overdose Rates - Tara L. Gallant, BA; Andrew R. Gilbert, BS; Sina Zargham, BA; Michael F. Di Lorenzo, MS; Jose L. Puglisi, PhD; Zachary R. Nicholas, MD; Valerie A. Gerriets, PhD (Elsevier, 2023)
Introduction: Ensuring that people at risk of overdosing on opioids have easy access to naloxone is an essential part of the fight against the opioid crisis. This study evaluates the impact of the 2016 California law (CA AB1535) permitting pharmacies to dispense this life-saving medication without a physician's prescription. Methods: California counties were categorized on the basis of population density (rural, suburban, urban), rate of opioid-related deaths by population density (high, medium, low), and rate of opioid prescriptions by population density (high, medium, low). Ten diverse pharmacies from each category were selected for inclusion. In a brief 1-minute interview conducted between July and August 2021, pharmacists from 146 California pharmacies were surveyed regarding their knowledge of CA AB1535, their practice of dispensing naloxone without a physician's prescription, and whether they normally stock naloxone. Chi-square tests were used to compare responses. Results: Although almost all pharmacies interviewed (94%) were aware of the law and most of them (64%) dispensed naloxone without a physician's prescription, few statistically significant differences were found between surveyed categories. There were no significant relationships between naloxone availability at pharmacies and overdose death rates. Conclusions: Our results suggest that the number of California pharmacies dispensing naloxone without a physician's prescription has continued to increase since the implementation of CA AB1535. However, despite increased access to naloxone at pharmacies, opioid overdose rates have continued to rise since 2016, indicating the need for a multifaceted harm reduction approach.